Bag of words and embedding text representation methods for medical article classification - Cichosz, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
Text classification has become a standard component of automated systematic literature review (SLR) solutions, where articles are classified as relevant or irrelevant to a particular literature study topic. Conventional machine learning algorithms for tabular data which can learn quickly from not necessarily large and usually imbalanced data with low computational demands are well suited to this application, but they require that the text data be transformed to a vector representation.
Keywords: text representation; text classification; bag of words; word embeddings